1995
DOI: 10.1002/cjce.5450730318
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficient of hydrogen in a Pd‐Ag membrane: Effect of hydrogen solubility

Abstract: The permeabilities of hydrogen through a Pd,,-Ag,, membrane have been measured at temperatures ranging from 423 to 573 K and under hydrogen pressure differences ranging from 69 to 256 kPa. From the available literature solubility data a neural network model has been developed in order to simulate the variation of the hydrogen content in the alloy as a function of pressure and temperature. Then, from steady state permeability measurements and calculated solubilities, the diffusion coefficients of hydrogen have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Instead, these approaches have used the approximation of representing the PdAg alloy as a cluster of 4 atoms in a face-centered cubic (fcc) arrangement with or without periodic boundary conditions. A system and approach used by these researchers does not provide the flexibility of estimating binding energy as well as solubility of PdAg and PdAu alloys with intermediate alloy compositions, hydrogen concentrations, and operating conditions (temperature, pressure) to find a suitable system composition and operating conditions for higher solubility. In addition, the errors associated with neglecting the effect of lattice expansion due to H on the binding energy/solubility are completely ignored under the assumption that they are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these approaches have used the approximation of representing the PdAg alloy as a cluster of 4 atoms in a face-centered cubic (fcc) arrangement with or without periodic boundary conditions. A system and approach used by these researchers does not provide the flexibility of estimating binding energy as well as solubility of PdAg and PdAu alloys with intermediate alloy compositions, hydrogen concentrations, and operating conditions (temperature, pressure) to find a suitable system composition and operating conditions for higher solubility. In addition, the errors associated with neglecting the effect of lattice expansion due to H on the binding energy/solubility are completely ignored under the assumption that they are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd–Ag resistivity measured in hydrogen (Figure 3) can be now overlapped by that obtained after the vacuum/desorption process at different absorption temperatures. Here, H/M was extrapolated by the literature data on the same kind of alloy [11,18,19,20,21,22]. By moving from right to left of the graph in Figure 8, i.e., following the temperature decrease starting from 450 °C, it is observed that: (1) in region A below 450 °C, the resistivity ρ i increases until a maximum was reached at ~200 °C, (2) in region B, a decrease is observed until a minimum in resistivity is reached at ~110 °C, and (3) in region C, there is a continuous increase of resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, both H/M [22,30,40,42,43,44] and D/M [18,21,22,23,31,45] were extrapolated by literature data on the same kind of alloy in order to compare solubility with resistivity data. The literature evidenced that at 100 kPa for low temperatures (25–70 °C) the D/M approaches the H/M value, while increasing the temperature (75–200 °C) causes the D/M to decreases faster, and only at high temperature (>300 °C) do both curves (H and D) tend to converge to very low values (close to zero).…”
Section: The Isotopic Effect On Pd-ag Resistivity and Solubilitymentioning
confidence: 99%